Solve Using the Square Root Property x^2+6x+10=0

Math
x2+6x+10=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=6, and c=10 into the quadratic formula and solve for x.
-6±62-4⋅(1⋅10)2⋅1
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅10)2⋅1
Multiply 10 by 1.
x=-6±36-4⋅102⋅1
Multiply -4 by 10.
x=-6±36-402⋅1
Subtract 40 from 36.
x=-6±-42⋅1
Rewrite -4 as -1(4).
x=-6±-1⋅42⋅1
Rewrite -1(4) as -1⋅4.
x=-6±-1⋅42⋅1
Rewrite -1 as i.
x=-6±i⋅42⋅1
Rewrite 4 as 22.
x=-6±i⋅222⋅1
Pull terms out from under the radical, assuming positive real numbers.
x=-6±i⋅22⋅1
Move 2 to the left of i.
x=-6±2i2⋅1
x=-6±2i2⋅1
Multiply 2 by 1.
x=-6±2i2
Simplify -6±2i2.
x=-3±i
x=-3±i
Simplify the expression to solve for the + portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅10)2⋅1
Multiply 10 by 1.
x=-6±36-4⋅102⋅1
Multiply -4 by 10.
x=-6±36-402⋅1
Subtract 40 from 36.
x=-6±-42⋅1
Rewrite -4 as -1(4).
x=-6±-1⋅42⋅1
Rewrite -1(4) as -1⋅4.
x=-6±-1⋅42⋅1
Rewrite -1 as i.
x=-6±i⋅42⋅1
Rewrite 4 as 22.
x=-6±i⋅222⋅1
Pull terms out from under the radical, assuming positive real numbers.
x=-6±i⋅22⋅1
Move 2 to the left of i.
x=-6±2i2⋅1
x=-6±2i2⋅1
Multiply 2 by 1.
x=-6±2i2
Simplify -6±2i2.
x=-3±i
Change the ± to +.
x=-3+i
x=-3+i
Simplify the expression to solve for the – portion of the ±.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise 6 to the power of 2.
x=-6±36-4⋅(1⋅10)2⋅1
Multiply 10 by 1.
x=-6±36-4⋅102⋅1
Multiply -4 by 10.
x=-6±36-402⋅1
Subtract 40 from 36.
x=-6±-42⋅1
Rewrite -4 as -1(4).
x=-6±-1⋅42⋅1
Rewrite -1(4) as -1⋅4.
x=-6±-1⋅42⋅1
Rewrite -1 as i.
x=-6±i⋅42⋅1
Rewrite 4 as 22.
x=-6±i⋅222⋅1
Pull terms out from under the radical, assuming positive real numbers.
x=-6±i⋅22⋅1
Move 2 to the left of i.
x=-6±2i2⋅1
x=-6±2i2⋅1
Multiply 2 by 1.
x=-6±2i2
Simplify -6±2i2.
x=-3±i
Change the ± to -.
x=-3-i
x=-3-i
The final answer is the combination of both solutions.
x=-3+i,-3-i
Solve Using the Square Root Property x^2+6x+10=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top